The success rate of intrauterine insemination in sperm preparation swim-up method at room temperature compared to the incubator temperature - Eriana Melinawati; Uki Retno Budihastuti; Mulyoto Pangestu; Teguh Prakosa; Affi Angelia Ratnasari; Abdurahman Laqif; Darto; Cahyono Hadi; Lunardhi Susanto; Metanolia Sukmawati; Rakano Kautsar Dwiyana; Alfi Marita Tristiarti; Abida Zuhra Jatiningtyas (Universitas Airlangga, 2023)
HIGHLIGHTS There were no significant differences in TMSC, sperm motility, sperm morphology, and DFI in sperm preparation using the swim-up method at 27°C and 37°C. However, this study provided an overview of the average improvement of DFI at 27°C compared to 37°C. There was no significant difference in the pregnancy rate of IUI in sperm preparation using the swim-up method at 27°C and 37°C. ABSTRACT Objective: This study aimed to determine the effect of temperature during sperm preparation on total sperm motile count (TMSC), sperm motility, sperm morphology, DNA fragmentation index (DFI), and pregnancy rate. Materials and Methods: A quasi-experimental laboratory study with pre- and post-test control group was conducted at Sekar Fertility Clinic, Dr. Moewardi General Hospital, Surakarta, Indonesia. A total of 20 sperm samples from infertile patients were prepared using the swim-up method at 27°C (group 1) and 37°C (group 2). TMSC, motility, morphology, and DFI examinations were performed. In addition, IUI was performed to confirm pregnancy rate. Sperm DNA fragmentation was determined using Sperm Chromatin Dispersion/SpermFunc DNAf test. Sperm DNA fragmentation was characterized by a halo <30% of the volume of the sperm head. Results: Group 1 had mean TMSC of 13.77 ± 9.30, while group 2 had 14.82 ± 8.82; p=0.218. Group 1 had a motility value 82.25+12.77 and group 2 had 82.55 ± 11.69; p=0.968. The morphological value for group 1 was 11.25 ± 5.15 and group 2 was 11.6 ± 5.34; p=0.626. The mean DFI for group 1 was 17.79 ± 10.88 and group 2 was 18.18 ± 12.95; p=0.765. Pregnancy rate in group 1 was 10% and group 2 was 20%; p=1.000. Conclusion: There were no significant differences in TMSC, sperm motility, sperm morphology, DFI, and pregnancy rate in sperm preparation using the swim-up method at 27°C and 37°C.